Impacto de la publicidad con el uso de las redes sociales de facebook y twitter, en las mypes comerciales de la ciudad de Huánuco - Salinas Alejandro, Niker (2017)
The micro and small enterprises in contemporary society at local, national and international level, are now a factor of growth and dynamism in the economic and social development of the region and the country, are not yet reached that leadership role to address this dynamic context, because they lack the economic , financial, technological and human resources that do not allow the strengthening and development sustained over time . One of the technological factors that lack the micro and small enterprises is the proper use of Information and Communication Technology (ICT). Besides the lack of a sense of partnership and business cooperation, not strategic alliances aimed at establishing business networks, prevents overcome barriers to reach the regional, national and international markets. Internal and external communication has become the cornerstone of any business and can not be outside of the new trends that rule the world of telecommunications. One type of communication is shaped by social networks. The appearance of these pathways changed the way to navigate the Internet. Many people and organizations use the web to  find a specific topic, but to connect with their friends via Facebook Twitter or any other similar network, this is an opportunity that companies can not be missed. Social networks have become the new advertising platform companies (other than size ) used to reach millions of consumers. “In Peru , the use of social networking is still not widespread , as in the case of micro- enterprises , 90 percent devotes its resources to sales and do not see social media a new way to announce “ said the president of the Peruvian Society of micro and small enterprises ( SPMYPES ), Jorge Panizo . In the present research work has made the following main question : What impact has on users , advertising implemented by micro and small business enterprises of the city of Huánuco , through social networks Facebook and Twitter ? which by the results obtained from users that constitute the population of 18 to 60 who have and use an email account as well as the owners and representatives , give answer to this question and the results are shown in the present work. The theoretical basis of the research was based on the fundamental concepts of social networking platforms on the Internet, as well as the components of the marketing mix of the scientific research process. What level has the characteristics of a descriptive and explanatory study , the research methods used were : descriptive , analytical and explanatory . The techniques used in the development of this work were: surveys, interviews, documentary analysis and navigation in Internet search engines , with their instruments , the latter allowed us to collect and process data. At the end of the investigation, the results obtained were: There is a high and frequent use of social networks Facebook and Twitter by the users, and activities that motivate users to continue to use social media is to keep in touch with family / friends and other entertainment. En look shows that users surveyed said the micro and small enterprises in a regular level placed publish and make promoting their products and services through social networks Facebook and Twitter. Most Facebook users speak little or mention products / services / companies through social network while 42.3% never do. Twitter users, although representing the minority , they tend to mention more often the products / services / companies through the social network. Regarding the desire / motivation felt by users to an intention to purchase or to find more information about products / services / companies, you can say it is not. To this point it could be concluded that the higher frequency of information seeking greater will be the motivation to make a purchase. On the other hand, it can be concluded that more than 50 % of respondents are very dissatisfied after trying a product / service met at a social network. But regardless of the level of dissatisfaction exists a large number of people who recommend products and services on the same social networks. Within social networks can make 4 promotional tools. Sales promotion, public relations, advertising and direct marketing. Generally you can see a very good acceptance of these tools by the users of social networks, but do not exert much influence on decision-making or user action